PROBLEMATIK YURIDIS SURAT KEPUTUSAN GUBERNUR BALI TENTANG RENCANA PEMANFAATAN, PENGEMBANGAN DAN PENGELOLAAN (REKLAMASI) WILAYAH PERAIRAN TELUK BENOA PROVINSI BALI - Trisna Adi Putra, I Komang; Wairocana, I Gusti Ngurah; Sudiarta, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 04, No. 01, Februari 2015)
Inception of Bali Governor's Decree No. 2138/02-C/HK/2012 are considered inviolation of Presidential Decree No. 122 of 2012 on Reclamation in Coastal Areas andSmall Islands are one of the article mentions reclamation should not be done in theconservation area. The method used is a normative legal research to know andunderstand how the validity of Bali Governor's Decree No. 2138/02-C/HK/2012 onGranting Permits and Use Rights, Development, and Management of Gulf waters ofBenoa Bali Area Jo Governor Decree No.1727/01-B/HK/2013 About Permit FeasibilityStudy Utilization Plan, Development, and Management of Benoa Gulf water BaliProvince. From the aspect of the substance that is the nomenclature of Bali GovernorDecree No. 2138/02-C/2012, is not in accordance with the provisions of Article 3paragraph (2) letter a Presidential Regulation No.122 of 2012, and the fourth Dictumquaternion Bali Governor's decision determines the activity initiator / permit holdershall implement (compiled) EIA, contrary to the dictum sixth.
Keywords: Bali, Reclamation, Conservation Areas, Bali Governor’s Decree